Customary Law and Natural Resource Governance: Strengthening Indigenous Rights in Environmental Management - Jaenong, Dhita Puthi; Ahimi, Liliana Nur; Zubaedillah, Zubaedillah (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
This study investigates the role of customary law in natural resource governance with a specific focus on strengthening the rights of Indigenous communities in Eastern Indonesia. The background of this research lies in the marginalization of customary law amid state-centered legal frameworks and the expansion of extractive industries, which often neglect Indigenous environmental stewardship. Using a qualitative case study approach, this research explores two Indigenous communities through in-depth interviews, participatory observation, and document analysis. The study identifies seven major themes—including traditional ecological practices, legal legitimacy, and institutional collaboration—based on thematic coding of 42 interview transcripts. Findings reveal that customary law serves as a culturally embedded regulatory system that effectively preserves biodiversity and maintains social harmony. In regions where formal recognition of customary land rights exists, communities demonstrate stronger environmental governance and reduced conflict. Conversely, areas lacking formal legal acknowledgment face greater legal uncertainty and ecological degradation due to state-imposed concessions. The study highlights the need for an inclusive legal framework that integrates customary and state law to ensure environmental justice. It also contributes conceptually by offering an interdisciplinary model combining juridical and socio-legal perspectives to analyze legal pluralism. This research affirms that customary law is not static but adapts dynamically to social and political changes. As such, the recognition and institutional integration of Indigenous legal systems are essential for achieving sustainable and equitable natural resource management.